قياس أثر النفقات العامة على البطالة في الجزائر - عزري, حميد; خوني, رابح (Université de M'sila, 2018)
تبحث هذه الدراسة أثر الانفاق العام على البطالة من خلال دراسة حالة الاقتصاد الجزائري خلال الفترة (2015-1990)، فتطرقنا في دراستنا القياسية إلى اختبار الاستقرارية باستخدام اختبار ديكي فولر الموسع ADF، ومن ثم اختبار وجود علاقة تكامل مشترك بطريقة أنجل-جرانجر، وأخيرا اختبار السببية جرانجر، ومن أهم نتائج الدراسة أنه إذا تغير النفقات العامة فإن البطالة لا تتغير، وكذلك فإن تغير البطالة لا يؤدي إلى تغير النفقات العامة وذلك بدرجة تأخر تساوي الواحد (1). This study examines the impact of public expenditure on unemployment by examining the state of the Algerian economy during the period 2015-1990. In our standard study, we examined the stability test using the ADF test, and then test the existence of a joint integration relationship with Angel Granger. The most important results of the study are that if public expenditure changes, unemployment will not change, and the change in unemployment will not lead to a change in public expenditure, with a delay of one (1).
Keywords: النفقات العامة، البطالة، الاستقرارية، التكامل المشترك، السببية.